2020
DOI: 10.1039/c9mh01390c
|View full text |Cite
|
Sign up to set email alerts
|

Reactive spinning to achieve nanocomposite gel fibers: from monomer to fiber dynamically with enhanced anisotropy

Abstract: This work presented a facile reactive spinning method for generating nanocomposite gel fibers with high anisotropy from monomers/nanoparticle hybrid precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…Engineered hydrogels and gel‐derived fibers are nascent and appealing soft matters, particularly in contexts of advanced wearables, [1–2] electronic devices, [3–5] drug delivery, [6] cosmetics, [7] food technology, [8] and smart behavior system, [9] due to their high stretchability, flexibility, hybrid networks, and diverse functionalities. However, those gel fibers show inferior mechanical properties, such as low fracture toughness, modulus, and strength (Table 1).…”
Section: Gel/fibers Solvent Tensilestrength [Mpa] Young's Modulus [Mpmentioning
confidence: 99%
“…Engineered hydrogels and gel‐derived fibers are nascent and appealing soft matters, particularly in contexts of advanced wearables, [1–2] electronic devices, [3–5] drug delivery, [6] cosmetics, [7] food technology, [8] and smart behavior system, [9] due to their high stretchability, flexibility, hybrid networks, and diverse functionalities. However, those gel fibers show inferior mechanical properties, such as low fracture toughness, modulus, and strength (Table 1).…”
Section: Gel/fibers Solvent Tensilestrength [Mpa] Young's Modulus [Mpmentioning
confidence: 99%
“…To overcome the low viscosity of monomer solutions, which leads to the breakage of nascent fiber, a precursor (containing monomers, initiators and crosslinkers) usually polymerizes in tubular templates, which are lubricated or super-hydrophobic [ 37 ]. Although fibrous hydrogels with millimeter levels of thickness (thin fibers are poorly demoldable) have been fabricated by such reactive spinning methods, its industrialization has encountered challenges to achieving high-speed manufacturing and obtaining fibers at the micrometer level [ 38 ]. In comparison, the more scalable spinning route in the textile industry is by constructing networks using macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent this issue, recently Ma et al reported a core–shell stretchable and conductive sodium polyacrylate hydrogel microfiber with a thin elastomer coating layer to prevent dehydration while maintaining good fiber elasticity 14. Nonetheless, the inert elastomer coating evitably leads hydrogel microfiber to be insensitive to environmental changes, which are unfavorable for sensing applications. Spinnability versus fiber strength: compared to electrospinning15,16 and extrusion spinning,9,10,17,18 microfluidic or draw‐spinning inspired from spider spinning procedure11–14,19,20 seems to be more suitable for fabricating long and uniform hydrogel microfibers. However, unless using the strategy of full dehydration, it is still challenging to compromise the spinnability and mechanical strength of hydrogel microfibers.…”
Section: Introductionmentioning
confidence: 99%
“…Spinnability versus fiber strength: compared to electrospinning15,16 and extrusion spinning,9,10,17,18 microfluidic or draw‐spinning inspired from spider spinning procedure11–14,19,20 seems to be more suitable for fabricating long and uniform hydrogel microfibers. However, unless using the strategy of full dehydration, it is still challenging to compromise the spinnability and mechanical strength of hydrogel microfibers.…”
Section: Introductionmentioning
confidence: 99%